Devoção mariana na Amazônia oriental: a irradiação do Círio de Nossa Senhora de Nazaré e o processo de ciriodificação no nordeste do Pará - Santos, João Paulo Siqueira dos (2019)
This present work of research involving the subject matter of “Círio de Nazaré” in Pará state intends demonstrating and analyzing how takes place the process of irradiation and diffusion of this sacred-profane event in some places, specifically, in the northeast region from this same state which produces a phenomenon denominated in thesis of: “Cirioedification”. Such Phenomenon exceeded the boundaries of the region on canvas and arrived in others Brazilian states, mainly, during the seventies of the twentieth century when “Círio” was broadcasted and boosted by others vectors. For we understand and interpret this phenomenon were identified and analyzed the responsible vectors of this expansion from event dedicated to “Our Lady of Nazareth” whose epicenter is the city of Belém city as well as Vigia municipality which is considered its historical nucleus, in other words, the birth or crib of the Nazarene devotion in Amazon region. At first this present study makes a theoretical and methodological approach for basing the understanding of the “Círio de Nazaré” from a conception of its humanistic and cultural geography, aiming concepts like cultural and devotional landscapes and the symbolic place constituted by its essential elements or by its geo-symbols come from Nazarene devotion; and next the Círio itself which is grasped as sacred-profane party religion in its interpretation while concept that establishes an atmosphere of various elements of this cult. From the creation of a model constituted of elements said essentials both Belém and Vigia were accomplished a comparative analysis of what happens in these two Círios and in others which take place in northeast of Pará for being identified through of a devotional landscape and of symbolic place, this is, to identify the effects of the “Círio de Nazaré” expansion and to notice others elements that are particularities of these places, and so to refer the phenomenon of the “Cirioedification”.